2009
DOI: 10.1002/ibd.20584
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and frequency of ophthalmologic manifestations in patients with inflammatory bowel disease: A prospective single-center study

Abstract: This study demonstrated the prevalence of the spectrum of ophthalmologic manifestations in the IBD population, including some rare and silent findings that may merit consideration and early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 26 publications
7
75
2
1
Order By: Relevance
“…We found a higher incidence of ophthalmological fundoscopy findings in evaluated patients comparing to previous studies (6)(7)(8)(9)(10) . Felekis et al also found similar high prevalence of posterior segment findings, but with no differentiation between primary, secondary or coincidental findings.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…We found a higher incidence of ophthalmological fundoscopy findings in evaluated patients comparing to previous studies (6)(7)(8)(9)(10) . Felekis et al also found similar high prevalence of posterior segment findings, but with no differentiation between primary, secondary or coincidental findings.…”
Section: Discussioncontrasting
confidence: 50%
“…Ophthalmological impairment is present in about 3.5% to 12% of IBD patients (6)(7)(8)(9) , and isn't directly correlated to intestinal mucocutaneous extension, usually occurs in IBD early years (8) . Possible ophthalmological findings are periocular edema, blepharitis, proptosis, conjunctivitis, scleritis, episcleritis, keratopathy, cataract, optic neuritis, optic, neuropathy, iridociclitis, retinal pigment epithelial atrophy, macular edema, serous retinal detachment and retinal hemorrhages (3,10) .…”
Section: Frequency Of Ophthalmological Posterior Segment Findings In mentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular manifestation in IBD were reported in 3.5%-43% cases; interestingly, they are more common in colonic or gastric CD cases similar to our case (8). There is limited information on the ocular involvement in adolescent and pediatric patients (9).…”
Section: Discussionsupporting
confidence: 66%
“…(3,4) Out of these, episcleritis, scleritis and uveitis are the most common ocular manifestations in adult IBD. (3,4) However, little is known of IBD in children. Although ocular manifestations usually occur early in the disease course, it is uncommon to have ocular manifestation preceding IBD diagnosis.…”
Section: Discussionmentioning
confidence: 99%